Design of triband antenna for telecommunications and network applications - Noor Qusay A. AlShaikhli; Mustafa Abdulkadhim Neamah; Mohammed Imad Aal-Nouman (Institute of Advanced Engineering and Science, 2022)
In today’s world, the need for multifunctioning with the minimum possible physical size of the appliances has gone very vast. This paper presents a novel triband microstrip antenna with two slit cuts that is designed and simulated by exploiting CST microwave studio suite 2016. Proposed antenna is composed of one square patch on the top layer and an incised ground bottom layer. Designed antenna operates on three wireless bands and can be utilized for various wireless and networking applications. Bands of interest are 3.3 GHz (lower WIMAX and possibly sub-6 GHz 5G applications), 4.5 GHz (data link system for UAV drones) and 5.8 GHz (WLAN). This work also focuses on the physical layer of the TCP/IP networking Paradigm model, the optimized design and fabrication in the physical layer is vital because any design issue will create a bottlenecking effect even if the upper networking layer were optimized. Designing an efficient wireless antenna will benefit service providers as they will depend on such robust physical layer to push more traffic reliably and efficiently. Antenna is low profile, with low fabrication cost. Antenna size is 29.6×30.5×1.5 mm3. Parameters such as input reflection coefficient and far-field radiation pattern have been simulated and analyzed.